Can a not-for-profit minority institutional shareholder make a big difference in corporate governance? A quasi-natural experiment - Ge, Wenxia; Ouyang, Caiyue; Shi, Zhenyang; Chen, Zhanliao (Journal of Corporate Finance, 2022)
In this study, we examine the effectiveness of the China Securities Investor Services Center (CSISC), a new minority shareholder protection mechanism promoted by the China Securities Regulatory Commission, in constraining earnings management. Employing a difference-in-differences analysis for a sample of Chinese listed companies during 2015–2017, we find that CSISC shareholding reduces earnings management. We also find that this effect exists in firms with weaker internal or external corporate governance mechanisms and in firms without political connections. The additional analyses show that the difference in earnings management between the treatment firms (i.e., CSISC-holding firms) and control firms is diminishing after the CSISC shareholding pilot program was promoted nationwide, and that CSISC shareholding also constrains controlling shareholders' tunneling. Our findings have important policy implications for emerging markets that attempt to improve minority shareholder protection.